Low-cost bench terracing and productive riser utilization in the Nilgiris - MURALIDHARAN, P; SAHOO, D C; MADHU, M; SUNDARAMBAL, P; MURUGAIAH, M (The Indian Journal of Agricultural Sciences, 2011)
A field study was conducted during 2003–06 at the research farm of the Central Soil and Water Conservation Research and Training Institute, Udhagamandalam to find out the suitable and economically viable medicinal or aromatic plant to be raised on the terrace risers to increase the productivity and returns from the terraced land, and to form vegetative terraces by establishing a vegetative barrier of geranium (Pelargonium graveolens L’Herit.) across the slope on a 25% sloping field. Medicinal and aromatic plants, viz geranium, cineraria (Cineraria maritima L.), and rosemary (Rosemarinus officinalis L.), were established on the risers of outward (5 and 10%) sloping terraces. The crop rotation of potato (Solanum tuberosum L.) – cabbage (Brassica oleracea L. var capitata L. f) in the first year and carrot (Daucus carota L.) – beans (Phaseolus vulgaris L.) in the second year was followed on the benches and 2 rotations completed in the study period. The highest net returns and potato equivalent yield was obtained from sloping field with strips of geranium as vegetative barrier across the slope. Among the medicinal/aromatic plants on the riser, cineraria and geranium performed well.